2022
DOI: 10.1093/advances/nmab145
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: Estrogen and the Risk of Cognitive Decline: A Missing Choline(rgic) Link?

Abstract: Factors that influence the risk of neurocognitive decline and Alzheimer's disease (AD) may provide insight into therapies for both disease treatment and prevention. While age is the most striking risk factor for AD, it is notable that the prevalence of AD is higher in women, representing two-thirds of cases. To explore potential underlying biological underpinnings of this observation, the intent of this article is to explore the interplay between cognitive aging and sex hormones, the cholinergic system, and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Results showed that social instability stress (SIS) linked to immobilization (IS) induced anxiogenic behavior more in ovariectomized than shamoperated animals, as reflected by OA parameters as well as GABA and serotonin levels assessments. Indeed, estrogens are known as potent modulators of neuronal physiology, although the exact mode of action by which estrogen exerts its diverse effects is not clear [42]. Nevertheless, it is almost certain that GABAergic and serotoninergic neurons are involved in estrogen modulators effects.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that social instability stress (SIS) linked to immobilization (IS) induced anxiogenic behavior more in ovariectomized than shamoperated animals, as reflected by OA parameters as well as GABA and serotonin levels assessments. Indeed, estrogens are known as potent modulators of neuronal physiology, although the exact mode of action by which estrogen exerts its diverse effects is not clear [42]. Nevertheless, it is almost certain that GABAergic and serotoninergic neurons are involved in estrogen modulators effects.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, estrogen therapy (ET) should be beneficial in this regard. However, conventional ET carries risks, including but not limited to cardiovascular liabilities as well as enhanced chances for the development of breast and uterine cancers, especially if it is used around geripause ( 80 83 ). Timing of ET is one of the critical factors.…”
Section: E2 and The Aging Female Brainmentioning
confidence: 99%
“…Notwithstanding, current ET carries contraindications due to the already mentioned risks for deep vein thrombosis and subsequent pulmonary embolism, estrogen-sensitive cancers, and additional adverse effects ( 40 , 80 , 82 , 83 ). This is, in large part, due to the significant peripheral exposure to the hormone and, thus, a significant increase in circulating estrogen(s) even when E2 is used for intervention instead of CEE.…”
Section: E2 and Vms (Hot Flushes)mentioning
confidence: 99%
“…Several studies have indicated that PEMT plays a vital role in nervous system diseases [122][123][124], and choline can alter mitosis and neuronal protein expression during fetal brain development [125]. Zhu et al [122,126] reported that PEMT deficiency increases progenitor cell mitosis and protein methylation and decreases calretinin levels in the embryonic mouse hippocampus (Table 1).…”
Section: Pemt and Othersmentioning
confidence: 99%